(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article presents ideas and methods for working on the tense category of the verb word group belonging to the group of independent word groups in elementary grades. This article is relevant in that it contains theoretical information about several methods, as well as guidelines for their practical application.